Penerapan Multimedia Interaktif Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Pemrograman - Lia Anggiani; Hendrika Rika; Nengsi Nengsi; Dian Dian; Maria Apriana (Jurnal Penelitian Teknologi Informasi dan Sains, 2023)
Programming is one of the fundamental subjects in the field of expertise in Technology, Information, and Communication (ICT). These topics must be mastered by all fields of study. Programming fundamentals remain alien to novices, such as the students in Class X. Basic programming subjects require a comprehensive understanding in order to be mastered. This study was carried out at SMK Negeri 1 Memperiwah Hulu. This investigation is a class action study with 35 class X TKJ 3 students as subjects. The data utilized in this investigation are learning outcomes. Indicators of research performance are based on the completion of learning outcomes for 75% of the student population. It can be seen from the image above that 30 students' learning outcomes fall into the decent category, with a percentage of 86%, and that 4 students fall into the sufficient category, with a percentage of 11%. Moreover, the percentage of students in the category of fewer learning outcomes amounted to one, with a percentage of 3%. Overall, the use of multimedia as a learning medium can enhance programming-related student learning outcomes. As an indicator of research success, in the first cycle it did not meet the set criteria for completeness, but in the second cycle it has increased and met the criteria. Increased activity and student learning outcomes are facilitated by the incorporation of multimedia skills and abilities into the activities of teachers.